Diagnostic performance of intestinal ultrasound compared with CT enterography in Crohn’s disease: single-center experience - Zhao, Yuanzhu; Fu, Qiong; Wang, Panpan; Wei, Shuru; Liu, Dan (Frontiers in Medicine, 2025)
AimThis study aimed to clarify the diagnostic value of transabdominal bowel ultrasonography (TBUS) examination for identifying the location of Crohn’s disease (CD) lesions and their complications in relation to computed tomography enterography (CTE).MethodsA retrospective analysis of the clinical data of 100 patients diagnosed with CD in our hospital from February 2022 to December 2023 was conducted. All patients underwent regular treatment after diagnosis, and CTE and TBUS examinations were performed at a 6-month (±2 weeks) follow-up after diagnosis. The efficacy of CTE examination and TBUS examination in diagnosing CD and its complications were compared through clinical diagnosis as a final criterion, and receiver operating characteristic (ROC) curves were drawn for diagnosis.ResultsThe sensitivity of both diagnostic methods for intestinal wall thickening was 96.94% (95/98), indicating no statistical significance (p > 0.05). No statistical significance in diagnostic efficacy in diagnosing CD complicated with intestinal stenosis was exhibited between the two examination methods (p > 0.05). No statistical significance in diagnostic efficacy in diagnosing CD complicated with intestinal fistula was exhibited between the two examination methods (p > 0.05). No statistical significance in diagnostic efficacy in diagnosing CD complicated with abdominal abscess was exhibited between the two examination methods (p > 0.05).ConclusionTBUS examination can achieve diagnostic results comparable to CTE, clearly displaying lesion site and intestinal segment structure of CD patients, and it exerts unique advantages in detecting extraintestinal complications. Thus, TBUS examination possesses high value in CD-assisted diagnosis and follow-up.